Faktor-Faktor Yang Mempengaruhi Return On Asset (Studi Kasus pada Bank Devisa di Indonesia Periode 2011 – 2015) - Dickky Nophiansah (UNSIKA (Universitas Singaperbangsa Karawang), 2018)
This research empirically examines the effect of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Net Interest Margin (NIM), interest rate, partially or simultaneously on Return On Asset (ROA) in Bank Devisa in Indonesia. This research is expected can give contribution to Economics development generally and financial management in particularly. This research uses descriptive and inductive method, i.e. data collecting, data processing, data analyzing, and data presentation, perform hypothesis testing, make inferences and suggestions.Keywords: ROA,CAR, NPL, NIM, BOPO, LDR, PDN